VALIDITAS PERMAINAN KARTU TRUTH AND DARE MATERI PENCEMARAN LINGKUNGAN UNTUK SISWA SMP KELAS VII - Gandha Tirta Bagus Renatha; Laily Rosdiana (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2020)
This study aims to describe the results of the validation of the Truth and Dare card game for seventh grade junior high school students on environmental pollution material. The media created are used to improve the learning outcomes of the remaining junior high schools based on validity, practicality and effectiveness. This research is a research development using the Research and Development (R&D) method which consists of five stages namely determination of potential and problems, information gathering, product design, review and revision, and validation. The data generated in the form of the results of the study sheet and the results of the validation sheet with 4 criteria namely linguistic criteria, presentation criteria, content criteria, and criteria for game functions. The Truth and Dare card game media review sheet aims to find things that are considered inappropriate for the Truth and Dare card game media. The results of the review sheets that have been reviewed are the linguistic criteria to reproduce the questions containing the C3 and C4 domains and the content criteria to adjust the game card points to the question domain. On the validation, sheet knows the validator's assessment of the level of eligibility or validity of the Truth and Dare card game media. In the validation sheet results obtained mode of 4 with a very decent category and a percentage of the validity of 97.6% with a very valid category. Then it can be concluded that the media of Truth and Dare card games as learning media on environmental pollution material is suitable for use in learning based on the results of studies and validation.